The nonuniform estimate of the convergence rate of the k-th maxima - Jokimaitis, Arvydas (Lietuvos matematikos rinkinys, 2009)
In this paper the nonuniform estimate of the convergence rate for the kth maxima of the independent identically distributed random variables is obtained.